Against racism - Scribano, Adrián Oscar (2020)
In the context of the COVID-19 pandemic, a disastrous event occurred in the United States, the death of George Floyd, the brutal murder of George Floyd. This event provoked numerous reactions of outrage, sadness, rejection and moral fatigue. Thousands of people throughout the United States, in Europe, in Latin America and across the rest of the world, demonstrated against racism in the context of the most widespread pandemic of recent centuries. Hundreds of thousands of people sensitized themselves, once again so far this century, to the “programmed” excesses of a capitalism that can only respond with death. In this framework, a group of friends and colleagues decided to deliver some words as untimely reflections on what happened, on its significance, on its meaning in context. The Center for Research and Sociological Studies proposed to prepare this Working Document which I am now pleased to present. Beyond stylistic refinement and editorial care, what is presented here are reflections of academics from three continents on what happened. Continuing the critical “dictum” of all the social sciences, the works presented here, brief but incisive, are the testimony of how multiple views and the diverse ways of seeing the world are necessary to elaborate a common criticism of all kinds of injustice and all kinds of inequality.